KAJIAN YURIDIS TERHADAP ALASAN PENGAJUAN ITSBAT NIKAH BERDASARKAN KOMPILASI HUKUM ISLAM (STUDI KASUS PENETAPAN PENGADILAN JAKARTA BARAT): Juridical Studies on Marriage Validation Application Reasons in Islamic Law Compilation Perspective (West Jakarta Court Determination Case Study) - Hanum Rachmi Adesti; Setyaningsih (Faculty of Law, Universitas Trisakti, 2025)
Marriage Validation is a legal process to legalize marriage that is not officially registered, aimed at providing legal certainty regarding the status of the marriage. The problem of this research examine reasons for submitting marriage validation in a Court Determination which has similar reasons but different results based on the Compilation of Islamic Law as well the extent to which the judge's considerations in two determinations comply with the provisions in Compilation of Islamic Law. This research uses normative approach by analyzing the provisions regulated in the Compilation of Islamic Law and related laws and regulations. The results of this research indicate that Determination No. 419/Pdt.P/2023/PA.JB was rejected because administrative reasons were deemed not urgent in accordance with Article 7 paragraph (1) Compilation of Islamic Law. On the other hand, Determination No. 419/Pdt.P/2023/PA.JB was accepted for more relevant reasons, namely marriage before the enactment of Law no. 1 of 1974, in accordance with Article 7 paragraph (1) letter d Compilation of Islamic Law. The conclusion emphasizes the importance of flexibility in the application of the law to achieve justice. Improving regulations and educating the public about the importance of marriage registration is needed to protect the legal rights of married couples.